2021
DOI: 10.1016/j.scitotenv.2021.145992
|View full text |Cite
|
Sign up to set email alerts
|

The spatial clustering analysis of COVID-19 and its associated factors in mainland China at the prefecture level

Abstract: Coronavirus disease 2019 (COVID-19) has become a worldwide public health threat. Many associated factors including population movement, meteorological parameters, air quality and socioeconomic conditions can affect COVID-19 transmission. However, no study has combined these various factors in a comprehensive analysis. We collected data on COVID-19 cases and the factors of interest in 340 prefectures of mainland China from 1 December 2019 to 30 April 2020. Moran's I statistic, Getis-Ord Gi ⁎ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 32 publications
2
35
2
1
Order By: Relevance
“…2 . Two provinces, Hubei and Hunan, were identified as the high-risk provinces ( Liu et al, 2021 ), seven were medium-risk provinces, such as Jiangsu, Anhui and Sichuan, and the Xinjiang Uygur Autonomous Region was selected as a low-risk province. Because about two thirds of total meat consumption in China is pork, pork was selected as the livestock product to assess the provincial agricultural product price differences, ( Xie et al, 2020 ), crucian carp, carp, and silver carp were selected as the aquatic products, based on the agricultural product types in the China Agricultural Price Survey Yearbook, celery cabbage, cucumber, beans and green pepper were selected as the representative vegetables, and Fuji apples, watermelons and bananas were selected as the representative fruit.…”
Section: Methodsmentioning
confidence: 99%
“…2 . Two provinces, Hubei and Hunan, were identified as the high-risk provinces ( Liu et al, 2021 ), seven were medium-risk provinces, such as Jiangsu, Anhui and Sichuan, and the Xinjiang Uygur Autonomous Region was selected as a low-risk province. Because about two thirds of total meat consumption in China is pork, pork was selected as the livestock product to assess the provincial agricultural product price differences, ( Xie et al, 2020 ), crucian carp, carp, and silver carp were selected as the aquatic products, based on the agricultural product types in the China Agricultural Price Survey Yearbook, celery cabbage, cucumber, beans and green pepper were selected as the representative vegetables, and Fuji apples, watermelons and bananas were selected as the representative fruit.…”
Section: Methodsmentioning
confidence: 99%
“…The analysis presented in this study is at the district level due to a lack of data availability at a smaller scale. Several studies have highlighted the potential of cluster analysis for identifying the spatial distribution of COVID-19 cases at a small scale (see for example, 53 , 54 , 55 ). Additionally, technological advancements like contract tracing applications have created new opportunities for identifying COVID-19 cases at a granular scale (see for example, 56 , 57 , 58 ).…”
Section: Discussionmentioning
confidence: 99%
“…The coronavirus disease 2019 (COVID-19), as a zoonotic disease, is a strain of severe acute respiratory syndrome that has posed severe global health challenges and affected human life quality. This pandemic has already resulted in extreme societal, economic, and political disruption worldwide ( Zambrano-Monserrate et al, 2020 ; Liu et al, 2021 ; Akrofi and Antwi, 2020 ; Teymourian et al, 2021 ). In a systematic review of physical measures to reduce respiratory virus transmission, handwashing was demonstrated to reduce transmission by 45–55% ( Jefferson et al, 2009 ; Brauer et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%